1999
DOI: 10.1300/j046v12n02_02
|View full text |Cite
|
Sign up to set email alerts
|

Market Segmentation of Green Consumers in Hong Kong

Abstract: Market segmentation is one of the useful tools for marketers to define target markets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
126
0
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(153 citation statements)
references
References 22 publications
15
126
0
12
Order By: Relevance
“…The items were obtained from Ivy et al (1998), Tilikidou (2007, and Abdul-Wahab (2008). Following Jain & Kaur (2006), Cottrell (2003), and Chan (1999), respondents answered these items as true, false, or not sure (McFarlane & Boxall, 2003). A composite knowledge score was calculated for each respondent by totaling the number of correct responses, which fell between 0 and 10.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The items were obtained from Ivy et al (1998), Tilikidou (2007, and Abdul-Wahab (2008). Following Jain & Kaur (2006), Cottrell (2003), and Chan (1999), respondents answered these items as true, false, or not sure (McFarlane & Boxall, 2003). A composite knowledge score was calculated for each respondent by totaling the number of correct responses, which fell between 0 and 10.…”
Section: Methodsmentioning
confidence: 99%
“…The study by Lee (2008) also reveals that young people are more concerned about the deterioration of environmental quality than their older counterparts. A few studies, however, report a non-significant or positive relationship between age and different environmental consciousness components (Chan, 1999;Shrum et al, 1995;Roberts, 1996).…”
Section: The Influence Of Socio-demographic Characteristics On Enviromentioning
confidence: 99%
“…In their study of 1600 households in Devon, UK, Gilg, Barr and Ford (2005) found that people could be categorized by a combination of two behavioral considerations: the kinds of activities that they undertook and how often (or consistently, see below) they performed these activities. Other studies center on how often people undertake the same activity (Chan 1999;Ozcaglar-Toulouse, Shiu and Shaw 2006), how consistently they behave (Neilssen and Scheepers 1992;Peattie 2001) or whether they undertake a few (different) activities or carry out a wide range of green or ethical activities (McDonald and Oates 2006). Studies that assess a range of different kinds of activities or look at use and disposal as well as point of purchase offer a richer picture of green or ethical consumption than single issue studies on the purchase of fair trade items, or recycling behavior, for example, would allow.…”
Section: Grouping Individuals Using Behavioral Constructsmentioning
confidence: 99%
“…Chan 42 sought to segment the market, based on the usage rate of green products, and to understand how the segments differed in terms of their demographic profi le, perception and attitude towards the purchase of green products. Consumers showing a high utilisation rate of these products ( Heavy Green Consumers ) were found to be more infl uenced by the opinions of other people, the government and environmentalist groups, had a strong sense of identity and were concerned about the environment.…”
Section: Behavioural Criteriamentioning
confidence: 99%